2018
DOI: 10.1302/1863-2548.12.180153
|View full text |Cite
|
Sign up to set email alerts
|

Availability of global health opportunities in North American Paediatric Orthopaedic Fellowship Programmes

Abstract: PurposeOrthopaedic residents are increasingly seeking international health electives (IHEs) during training, many of which involve providing paediatric orthopaedic care. However, little is known about the availability of IHEs during orthopaedic fellowship training. Our study sought to assess the global health opportunities available to North American paediatric orthopaedic fellows.MethodsWe conducted an online, REDCap-based survey of paediatric orthopaedic fellowship programme directors (PDs) in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Multiple studies have investigated trainee perceptions to Global Surgery and many cited absence of funding, minimal support from home institutions, and lack of established partner sites as obstacles to undertaking an international placement. 7,9 The results from this analysis showed that a higher proportion of the fellowships offered to LMIC trainees included funding as opposed to those solely for HIC trainees. This seems encouraging if fellowships are to be financially viable for all.…”
Section: Local Infrastructure 1 Advocacymentioning
confidence: 88%
See 1 more Smart Citation
“…Multiple studies have investigated trainee perceptions to Global Surgery and many cited absence of funding, minimal support from home institutions, and lack of established partner sites as obstacles to undertaking an international placement. 7,9 The results from this analysis showed that a higher proportion of the fellowships offered to LMIC trainees included funding as opposed to those solely for HIC trainees. This seems encouraging if fellowships are to be financially viable for all.…”
Section: Local Infrastructure 1 Advocacymentioning
confidence: 88%
“…There is currently also a discrepancy between the rising interest in global surgery in trainees with the availability of placements, indicating the need for more accessible and effective appointments. [7][8][9] Global Surgery Fellowships Davison et al…”
Section: Discussionmentioning
confidence: 99%
“…The person has to come on a slightly regular basis, maybe once a year" 45 . Strong models of longitudinal partnerships in the orthopaedic literature [46][47][48][49] are considerate of LMIC capacity, including adequate surgical volume and faculty supervision to support visiting residents, and to ensure that residents operate within their training level 46,47,50,51 . These models rely on ongoing interest and investment of both LMIC and HIC orthopaedic faculty, and designated LMIC and HIC program director responsible for ongoing management 46,47,50,51 .…”
Section: Discussionmentioning
confidence: 99%